THE DEVELOPMENT ELECTRONIC BOOK TO DEVELOP WRITING THAI LANGUAGE FOR THE 1ST YEAR UNDERGRAGUATE STUDENTS LOPBURI COLLEGE OF DRAMATIC ARTS - Posritong, Preampree (Journal of MCU Nakhondhat, 2023)
The purpose of this study was 1) develop and determine the efficiency of the electronic book (E-Book) “Thai Writing for the First-Year Students of Lop Buri College of Dramatic Arts” according to the efficiency criteria, 2) compare the academic achievements of the students before and after using the E-book and 3) discover their satisfaction with the E-book. It is experimental research. The target group is the first-year students of the Bachelor of Education program at Lop Buri College of Dramatic Arts who enrolled in the 300-12001 Thai for Communication course in the first semester of the academic year 2021. The research instruments consisted of 1) the E-Book “Thai Writing for the First-Year Students of Lop Buri College of Dramatic Arts”, 2) a learning management plan for the use of the E-Book 3) pre- and post-achievement tests before and after using the E-Book and 4) a student satisfaction questionnaire with the E-Book. The statistics used to analyze the data were mean ( ), standard deviation ( ), percentage, and t-test dependent. The results are as follows: 1) The E-Book “Thai Writing for the First-Year Students of Lop Buri College of Dramatic Arts” developed by the researcher obtained an efficiency of 82.30/82.81, which met the specified criteria of 80/80. 2) Based on the comparison of their academic achievement scores before and after using the E-Book, overall, the students receivedhigher academic achievement after using the E-Book at a statistical significance of .05. 3) Regarding their satisfaction with the E-book, the overall satisfaction of the students was at a high level ( = 4.30, = 0.72)